Global Adaptation to a Lipid Environment Triggers the Dormancy-Related Phenotype of Mycobacterium tuberculosis - Juan G. Rodríguez (American Society for Microbiology, 2014)
ABSTRACT Strong evidence supports the idea that fatty acids rather than carbohydrates are the main energy source of Mycobacterium tuberculosis during infection and latency. Despite that important role, a complete scenario of the bacterium’s metabolism when lipids are the main energy source is still lacking. Here we report the development of an in vitro model to analyze adaptation of M. tuberculosis during assimilation of long-chain fatty acids as sole carbon sources. The global lipid transcriptome revealed a shift toward the glyoxylate cycle, the overexpression of main regulators whiB3, dosR, and Rv0081, and the increased expression of several genes related to reductive stress. Our evidence showed that lipid storage seems to be the selected mechanism used by M. tuberculosis to ameliorate the assumed damage of reductive stress and that concomitantly the bacilli acquired a slowed-growth and drug-tolerant phenotype, all characteristics previously associated with the dormant stage. Additionally, intergenic regions were also detected, including the unexpected upregulation of tRNAs that suggest a new role for these molecules in the acquisition of a drug-tolerant phenotype by dormant bacilli. Finally, a set of lipid signature genes for the adaptation process was also identified. This in vitro model represents a suitable condition to illustrate the participation of reductive stress in drugs’ activity against dormant bacilli, an aspect scarcely investigated to date. This approach provides a new perspective to the understanding of latent infection and suggests the participation of previously undetected molecules. IMPORTANCE Mycobacterium tuberculosis establishes long-lasting highly prevalent infection inside the human body, called latent tuberculosis. The known involvement of fatty acids is changing our understanding of that silent infection; however, question of how tubercle bacilli globally adapt to a lipid-enriched environment is still an unanswered. With the single change of providing fatty acids as carbon sources, the bacilli switch on their program related to dormant stage: slowed growth, accumulation of lipid bodies, and development of drug tolerance. In this stage, unexpected and previously unknown participants were found to play putatively important roles during the process. For the first time, this work compares the global transcriptomics of bacteria by using strand-specific RNA sequencing under two different growth conditions. This study suggests novel targets for the control of tuberculosis and provides a new straightforward in vitro model that could help to test the activity of drugs against dormant bacilli from a novel perspective.